(untitled) (American Journal of Islam and Society, 2001)
Science Without Philosophy? Many of our readers and contributors have raised questions regarding the various definitions of social science and their relation to the scope of MISS. Definitions of social science have changed with time and place, and one of the reasons for that is not what is “social,” but what is “science”? “Science” in French, or “wissenschaft” in German, do not translate exactly the same as “science” in English. In English speaking world, “science” has an association with hard sciences while social sciences have been tacitly considered to be soft sciences, or not sciences at all. Such a distinction does not exist in other languages. It is not our intent here to provide a mere taxonomy of the meanings of science, but to develop an understanding as well as a consensus that social sciences and their sub-disciplines are, without exception, based on certain paradigms that are philosophical in nature. Being a social scientist without the knowledge of these philosophical assumptions, upon which the paradigms of the socia1 sciences rest, is to willingly escape the full picture. Proper philosophical training, therefore, has a deep nexus with the methods of social science, and constitutes a necessary pre-requisite of understanding the paradigms. Paradigms establish the agenda and the agenda dictates the policy. social sciences therefore become a vehicle of understanding the society in consonance with the accepted philosophical truths. Philosophical exposition of concepts and ideas in turn necessitates a definition of philosophy itself. All definitions of philosophy will point to certain “givens” or a priori assumptions that precede all scientific inquiry. If social sciences stay within the realm of the positivist paradigm, the problem may seemingly be solved, but reducing inquiry to empiricism has its own pitfalls and the atomistic division in today’s academia is a direct result of that. Further, it restricts the scope of those social scientists who also happen to be believers in transcendental Truth. Conversely, to the degree that philosophy is ...